Menguatkan Iman Kepada Allah SWT Sebagai Asas Pendidikan Aqidah Islam - Luqman Hakim (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Strengthening aqidah through education is a basic need, because aqidah is the main foundation and basis of Islamic teachings. In another example, everything that exists in this universe is a bias from the existence of Allah SWT. belief in the existence of this universe, actually leads to the fact that